Comparison of tetrodotoxin uptake and gene expression in the liver between juvenile and adult tiger pufferfish, Takifugu rubripes. (1st March 2016) - Kiriake, Aya; Ohta, Akira; Suga, Emi; Matsumoto, Takuya; Ishizaki, Shoichiro; Nagashima, Yuji
Abstract: Marine pufferfish of the family Tetraodontidae accumulate high levels of tetrodotoxin (TTX). The profile of TTX accumulation is reported to differ between tiger pufferfish Takifugu rubripes juveniles and adults administered TTX. Adults mainly accumulate TTX in liver, while juveniles transfer TTX from the liver to the skin. In the present study, we investigated TTX uptake into liver tissue slices of T. rubripes juveniles (4-month-old) and adults (18-month-old) in an in vitro incubation experiment, and compared their differential gene expression profiles in the liver by suppression subtracted hybridization (SSH). The tissue culture experiment revealed that TTX uptake in the liver itself was indistinguishable between the juveniles and the adults. In SSH analysis, a total of 176 clones were upregulated in the juvenile liver, the majority of which comprised hemoglobin subunit alpha-2-like gene (53 clones), hemoglobin subunit beta-like gene (40 clones), and type-4 ice-structuring protein LS-12-like gene (20 clones). A total of 211 clones were upregulated in the adult liver, including serotransferrin-like gene (84 clones), fibrinogen beta chain-like gene (15 clones), and 14 kDa apolipoprotein gene (10 clones). Based on these and previous findings on genes related to TTX intoxication in pufferfish, serotransferrin-like gene, complement C3-like gene, water-temperature-acclimation-related-65 kDa-protein-like gene, and chymotrypsin elastase family member 2A-like gene appear to be involved in TTX toxification of the T. rubripes liver. Highlights: Pufferfish Takifugu rubripes adults accumulate mainly tetrodotoxin (TTX) in liver. In contrast, pufferfish juveniles transferred TTX from the liver to the skin. However, there was no difference in TTX uptake in liver tissue slices between them. Genes expressed differentially in juvenile and adult liver were analyzed by SSH. SSH cDNA libraries revealed candidate genes of T. rubripes liver toxification.